Sustained photodynamic effect of single chirality-enriched single-walled carbon nanotubes. (May 2020) - Fukuda, Ryosuke; Umeyama, Tomokazu; Tsujimoto, Masahiko; Ishidate, Fumiyoshi; Tanaka, Takeshi; Kataura, Hiromichi; Imahori, Hiroshi; Murakami, Tatsuya
Abstract: Semiconducting single-walled carbon nanotubes (s-SWNTs) are capable of fluorescence emission as well as photothermal and photodynamic actions, resulting from their near-infrared (NIR) absorptions corresponding to their S11 and S22 transitions. Here, we show that one chiral s-SWNTs, (6, 4)-SWNTs, photogenerates all three of the major reactive oxygen species, i.e., singlet oxygen ( 1 O2 ), superoxide anion (O2 – ), and hydroxyl radical ( OH), in a sustainable manner. Its efficiency for OH generation is dramatically higher than those of the other two chiral s-SWNTs tested, as well as a clinical NIR dye. This sustained and relatively high photodynamic effect in (6, 4)-SWNTs is due to their extraordinary high photostability and relatively high generation efficiency of their triplet excited state. In the colloidal stabilization of (6, 4)-SWNTs under physiological conditions, a serum protein consisting of a tandem repeat of amphiphilic α-helices is found to be useful for dispersion. The protein-coated (6, 4)-SWNTs are capable of effectively ablating cancer cells and disintegrating amyloid beta peptide aggregates through sustained photodynamic action. Graphical abstract: Image 1